Innovation in Aviation Education: Development of a Web-Based Flight Simulator Management System (FSMS) at Pilot Academy - Hadi Prayitno; Putra Wicaksono; Iwan Engkus Kurniawan; Efendi Efendi (STAI Hubbulwathan Duri, 2023)
The main objective of this study is to optimise the documentation process for simulator administration in compliance with regulatory norms. This will allow both the simulator administrator and operations administrator to efficiently strategize the utilisation of the simulator, while also providing management with easy access to documented results. The research methodology utilized in this investigation is the ADDIE research model, which encompasses Analysis, Design, Development, Implementation, and Evaluation. The results of this research illustrate that the Flight Simulator Management System (FSMS) information system operates effectively, incorporating various menu pages. These menu pages include a dashboard, simulator schedule, simulator checklist, simulator log book, simulator maintenance, simulator malfunction, reports, database summary, cadet data, flight instructor data, and user data. The results of the validation of the three experts have an average value of 3.41 or are classified as good criteria. These results are obtained by looking at the usability aspect with an average value of 3.27, while the design aspect obtains an average value of 3.53, and the operational aspect obtains an average value of 3.44. the validation results of ten users have an average value of 3.37 or are classified as good criteria. These results were obtained by looking at the truth aspect with an average value of 3.30, while the effectiveness aspect obtained an average value of 3.34 and the operational aspect received an average value of 3.47.